IgG4-Related Tubulointerstitial Nephritis Associated with Membranous Nephropathy in Two Patients: Remission after Administering a Combination of Steroid and Mizoribine - Kana N. Miyata; Hiromi Kihira; Manabu Haneda; Yasuhide Nishio (Case Reports in Nephrology)
We report two cases of Japanese men who presented with proteinuria, eosinophilia, hypocomplementemia, and high serum immunoglobulin G4 (IgG4) concentration and were diagnosed with membranous nephropathy associated with IgG4-related tubulointerstitial nephritis on renal biopsy. The typical renal lesions of IgG4-related disease are tubulointerstitial nephritis, which improves remarkably with steroid therapy, and occasional glomerular changes. In our two cases, renal biopsy revealed IgG4-positive immune complex deposits in glomeruli in a pattern of membranous nephropathy and concurrent tubulointerstitial nephritis with IgG4 plasma cells. In both cases, proteinuria persisted with initial prednisolone treatment and was resolved only after the addition of mizoribine. We report the first two cases in which the combination of prednisolone and mizoribine was effective for treating membranous nephropathy associated with IgG4-related tubulointerstitial nephritis.